2023
DOI: 10.1111/fcp.12924
|View full text |Cite
|
Sign up to set email alerts
|

KATP channels are regulators of programmed cell death and targets for the creation of novel drugs against ischemia/reperfusion cardiac injury

Abstract: BackgroundThe use of percutaneous coronary intervention (PCI) in patients with ST‐segment elevation myocardial infarction (STEMI) is associated with a mortality rate of 5%–7%. It is clear that there is an urgent need to develop new drugs that can effectively prevent cardiac reperfusion injury. ATP‐sensitive K+ (KATP) channel openers (KCOs) can be classified as such drugs.ResultsKCOs prevent irreversible ischemia and reperfusion injury of the heart. KATP channel opening promotes inhibition of apoptosis, necropt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 341 publications
0
6
0
Order By: Relevance
“…Another myocyte study found that diazoxide was protective against apoptosis, although protection depended on the timing of treatment [130] . The cardioprotection associated with diazoxide in a swine model was found to result from decreased myocyte apoptosis and mitochondrial damage [131] . Recent reviews have also discussed the inhibition of apoptosis as a potential mechanism of K ATP channel modulation in cardioprotection [132] .…”
Section: Mitochondrial Respirationmentioning
confidence: 97%
“…Another myocyte study found that diazoxide was protective against apoptosis, although protection depended on the timing of treatment [130] . The cardioprotection associated with diazoxide in a swine model was found to result from decreased myocyte apoptosis and mitochondrial damage [131] . Recent reviews have also discussed the inhibition of apoptosis as a potential mechanism of K ATP channel modulation in cardioprotection [132] .…”
Section: Mitochondrial Respirationmentioning
confidence: 97%
“…However, GLP-1(7-36) inhibits K ATP channels in β-cells of the islets of Langerhans, which leads to increased insulin secretion [122]. It should be noted that K ATP channels in cardiomyocytes and in β-cells are different [123]. Apparently, this feature of K ATP channels allows GLP-1 to block them in β-cells and activate them in cardiomyocytes.…”
Section: Glp-1 Prevents the Development Of Adverse Remodeling Of The ...mentioning
confidence: 99%
“…In contrast, the activation of GSK-3β aggravates I/R injury of the heart [83]. K ATP channels, big conductance Ca 2+activated K + channels (BK Ca channels), and MPT pores are involved and are hypothetical end-effectors of ischemic pre-and postconditioning [18,83,123]. It has been found that K ATP channel opening, BK Ca channel opening, and MPT pore closing promote an increase in cardiac tolerance to I/R [123,142,143].…”
Section: The Signaling Mechanism Of the Cardioprotective Effect Of Gl...mentioning
confidence: 99%
“…Maintaining mitochondrial volume homeostasis is essential for preserving vesicle integrity during membrane transport with high variations in ions and water, which is crucial for ATP generation [ 140 ]. Additionally, it helps in preventing the occurrence of ventricular arrhythmias and improving survival rates during cardiac I/R [ 141 ].…”
Section: Application Of Ion Channel Therapy In MImentioning
confidence: 99%